Development of a defined compost system for the study of plant-microbe interactions - Masters-Clark, Emily; Shone, E.; Paradelo, M.; Hirsch, Penny R.; Clark, Ian M.; Otten, Wilfred; Brennan, Feargal P.; Mauchline, Tim H. (Nature Publishing Group, 2020)
Plant growth promoting rhizobacteria can improve plant health by providing enhanced nutrition, disease suppression and abiotic stress resistance, and have potential to contribute to sustainable agriculture. We have developed a sphagnum peat-based compost platform for investigating plant-microbe interactions. The chemical, physical and biological status of the system can be manipulated to understand the relative importance of these factors for plant health, demonstrated using three case studies: 1. Nutrient depleted compost retained its structure, but plants grown in this medium were severely stunted in growth due to removal of essential soluble nutrients - particularly, nitrogen, phosphorus and potassium. Compost nutrient status was replenished with the addition of selected soluble nutrients, validated by plant biomass; 2. When comparing milled and unmilled compost, we found nutrient status to be more important than matrix structure for plant growth; 3. In compost deficient in soluble P, supplemented with an insoluble inorganic form of P (Ca3(PO4)2), application of a phosphate solubilising Pseudomonas strain to plant roots provides a significant growth boost when compared with a Pseudomonas strain incapable of solubilising Ca3(PO4)2. Our findings show that the compost system can be manipulated to impose biotic and abiotic stresses for testing how microbial inoculants influence plant growth.